Ceric Cyclopentadienides Bearing Alkoxy, Aryloxy, Chlorido, or Iodido Co‐Ligands. Issue 50 (12th May 2017) - Schneider, David; Harmgarth, Nicole; Edelmann, Frank T.; Anwander, Reiner
Abstract: A series of heteroleptic tris(cyclopentadienyl) Ce IV complexes has been isolated and crystallographically characterized, revealing the broad accessibility of such organocerium(IV) compounds. The oxidation of complexes Cp Me 3 Ce(thf) and Cp′3 Ce(thf) (Cp Me =C5 H4 Me, Cp′=C5 H4 SiMe3 ), bearing monosubstituted electron‐poor cyclopentadienyl ligands, with 0.5 equivalents of 1, 4‐benzoquinone or C2 Cl6 gave the cerium(IV) hydroquinolate complexes Cp Me 3 Ce(OC6 H4 O)CeCp Me 3 and Cp′3 Ce(OC6 H4 O)CeCp′3, or the chloride complexes Cp Me 3 CeCl and Cp′3 CeCl, respectively; the iodide complex Cp′3 CeI was obtained from the reaction of Cp′3 Ce(thf) with elemental iodine. The behavior of Cp′3 CeCl in salt metathesis protocols employing alkali metal amides or alkyl, alkoxide, and aryloxide reagents was investigated, which gave rise to the robust and isolable cerium(IV) alkoxide Cp′3 Ce(O t Bu). Trivalent [Cp′2 CeCl]2 was synthesized by AlMe4 →Cl exchange utilizing Cp′2 Ce(AlMe4 ) and AlMe2 Cl. The reactivity of [Cp′2 CeCl]2 towards the oxidants Ph3 CCl, C2 Cl6, 1, 4‐benzoquinone, and I2 has been assessed, and has provided useful information on Ce III /Ce IV redox deactivation pathways. In addition to X‐ray structure analysis, all the complexes were characterized by NMR, DRIFT (diffuse reflectance IR Fourier transform), and UV/Vis spectroscopy as well as elemental analysis. The tetravalent compounds were further analyzed for their magnetic susceptibility by using Evans' method. Abstract : Organocerium complexes : Tris(cyclopentadienyl) scaffolds provide broad access to tetravalent organocerium complexes. The application of a diverse set of oxidants gives new insights into the oxidizability of homo‐ and heteroleptic cyclopentadienyl cerium(III) compounds (see scheme). All new compounds have been characterized by spectroscopy and X‐ray diffraction.